Konflik Beban Ganda Bidan Di Puskesmas - Budi Astyandini; Khobibah Khobibah; Heny Rosiana (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
The alignment of the roles of men and women has the result of women's involvement in the field of work due to biological faktor s, technological advances, and the human desire to work as a form of self-actualization. This research method is quantitative with a descriptive approach. The research was conducted at 3 Community Health Centers with a population of 30 midwives who worked outpatient care at Health Centers in the Kendal district in October 2022. Data collection used primary data by distributing questionnaires through the Google form which were distributed to midwives who had given informed consent. A small part of the conflict that occurred with midwives working at the Puskesmas was having problems when carrying work at home because their partners also worked and had been midwives for a long time. so that adaptation has occurred, and problems at home do not affect midwives when performing their duties at the outpatient Health Center because the tasks are carried out with full commitment.